2022
DOI: 10.1186/s12903-022-02488-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biofilm formation on acrylic resins used to fabricate dental temporary restorations with the use of 3D printing technology

Abstract: Background Temporary implant-retained restorations are required to support function and esthetics of the masticatory system until the final restoration is completed and delivered. Acrylic resins are commonly used in prosthetic dentistry and lately they have been used in three-dimensional (3D) printing technology. Since this technology it is fairly new, the number of studies on their susceptibility to microbial adhesion is low. Restorations placed even for a short period of time may become the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Their results showed that CAD/CAM PMMA-based polymers had less surface roughness and less adhesion of Candida albicans. Mazurek et al [ 44 ] evaluated biofilm formation on 3D-printed temporary restorations and assessed the post-processing impact on microbial adhesion. They found that roughness itself was not the main factor affecting microbial adhesion to 3D-printed resin.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that CAD/CAM PMMA-based polymers had less surface roughness and less adhesion of Candida albicans. Mazurek et al [ 44 ] evaluated biofilm formation on 3D-printed temporary restorations and assessed the post-processing impact on microbial adhesion. They found that roughness itself was not the main factor affecting microbial adhesion to 3D-printed resin.…”
Section: Discussionmentioning
confidence: 99%
“…The complex chemical compositions of novel dental provisional implant restorations fabricated by different techniques have been the subject of various studies [ 10 , 16 , 17 , 20 ]. It has been reported that incomplete polymerization of the material and the presence of toxic monomers can negatively affect the biologic response, particularly after surgical procedures such as implant placement where the provisional restoration is in close contact with the surgical site [ 8 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have investigated the mechanical properties of provisional CAD/CAM restorations [ 11 15 ], few studies have focused on the biological response of these materials, especially in the context of provisional implant restorations [ 16 , 17 ]. Provisional restorations are close contact with gingival tissue, hence ensuring their biocompatibility and promoting tissue integration are of paramount importance to prevent any adverse reactions in the adjacent tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the literature reports that deficiencies resulting from the polymerization contraction of composite resins persist [7,18]. Shrinkage is a physical process inherent to the healing reaction and causes tension at the toothrestoration interface that can lead to marginal microleakage of oral fluids and microorganisms.…”
Section: Major Findings -Composite Resin and Biofilmmentioning
confidence: 99%